Critical alliance - Goddard, Elizabeth (Goddard, Elizabeth. Rocky Mountain courage, 2022)
Mackenzie Hanson's special set of skills opened the door to a successful career as a professor of cybersecurity at a Michigan university, allowing her to put her criminal past behind her. When a long-ago partner in crime delivers a cryptic message about her father's tech company being under cyberattack, she heads for Montana to secure exposed assets, close security breaches, and hopefully save lives. Diplomatic Security Services special agent Alex Knight is back home in Montana to decompress from a mission gone wrong. But he's drawn into another mystery, complete with suspicious deaths, lethal threats, and whispers of espionage that all have one thing in common--a beautiful cybersecurity expert with a dark past. When the situation turns deadly, Alex and Mackenzie will have to work together to find the answers they need, before someone silences Mackenzie for good.